Expression of tumor necrosis factor alpha-induced protein 6 messenger RNA in porcine preovulatory ovarian follicles - Nagyova, Eva; Nemcova, Lucie; Prochazka, Radek (The Journal of reproduction and development, 2009)
It has been shown previously that tumor necrosis factor alpha-induced protein 6 (TNFAIP6) is essential for formation of the cumulus extracellular matrix and female fertility. Therefore, we studied the expression of TNFAIP6 mRNA in porcine preovulatory follicles. In addition, we asked whether the expression of TNFAIP6 mRNA changes in mural granulosa cells (MGCs) during the periovulatory period or after culture of oocyte-cumulus complexes (OCCs) or MGCs in vitro. Mural granulosa cells obtained from follicles on day 12 (D 12) and day 15 (D 15) of the estrous cycle, eCG-stimulated follicles, follicles at 4-32 h after hCG stimulation and MGCs and OCCs obtained from immature gilts and cultured for 0-44 h in vitro with gonadotropins were used for extraction of total RNA and assessment of the relative abundance (RA) of TNFAIP6 mRNA by reverse transcription-polymerase chain reaction (RT-PCR). The levels of TNFAIP6 mRNA were low in the follicles on D 12 and D 15 of the estrous cycle and at 66 h after eCG stimulation but were significantly increased at 4 h after hCG. The high level of TNFAIP6 expression was maintained until 16 h after hCG stimulation and gradually decreased at 24 and 32 h after hCG. During in vitro culture, FSH/LH-induced TNFAIP6 mRNA was expressed in both OCCs and MGCs in a similar temporal pattern as seen in vivo. We conclude that TNFAIP6 expression in the pig, like other species, increases in preovulatory follicles following the LH (hCG) surge. The OCC and MGC display similar patterns of TNFAIP6 expression under both in vivo and in vitro conditions.
Keywords: Animals; Female; molekuly buněčné adheze; Tissue Distribution; Tumor Necrosis Factor-alpha; ženské pohlaví; ovariální folikul; prasata; messenger RNA; kultivované buňky; RNA, Messenger; Cells, Cultured; TNF-alfa; Swine; Cell Adhesion Molecules; ovulace; tkáňová distribuce; exprese genu; Ovulation; zvířata; Ovarian Follicle; Gene Expression